THE EFFICACY OF HIGH-DOSE CONSOLIDATION AND AUTOLOGOUS BONE MARROW TRANSPLANTATION IN FIRST REMISSION OF ACUTE MYELOID LEUKEMIA - I. A. Samorodova; S. N. Bondarenko; V. N. Ovechkina; A. V. Klimovich; E. I. Podolceva; N. V. Medvedeva; A. S. Nizamutdinova; E. V. Karyagina; B. I. Smirnov; I. S. Moiseev; L. S. Zubarovskaya; B. V. Afanasyev (Онкогематология, 2018)
Introduction. The question of the most adequate treatment strategy of AML in cases when it is impossible to perform allogeneic HSCT because of any reason still remains open.The aim of this study was to assess the long-term survival of patients with AML who received chemotherapy (CT) or autologous HSCT as consolidation in the first remission of the disease. It was included 135 patients aged 18 to 67 years, with a verified diagnosis of AML (except FAB M3) in the study. Of these, 100 patients received only CT, 35 patients received consolidation with autologous bone marrow transplantation. Patients who achieved remission after completion of induction CT courses received one of three treatment options as consolidation: 1) chemotherapy of standard-intensity (sCT), 2) high-dose chemotherapy (HDCT), 3) autologous HSCT (autoHSCT) conducted after 1–2 courses of high-dose CT. Adverse prognostic factors were identified as: age over 40 years, hyperleucocytosis more than 50,0 × 10 9/L and unfavorable cytogenetic and molecular-biological risk group.Materials and methods. Depending on the number of prognostic factors at the onset of disease relapse-free survival (RFS) was 47 % in their absence, 45 % in the presence of 1 factor, in the presence of 2 factors – 14 % (p = 0,000), regardless of the variant of consolidation therapy (sCT, HDCT, autoHSCT). A high level of white blood cells adversely affects OS (38 % vs. 22 %) and increases the frequency of relapse (52 % vs. 69 %) when performing only CT (sCT and HDCT). At initial white blood cells level more than 50,0 × 10 9/L the 5-year OS was 60 % when performing both autoHSCT and HDCT. Performance of autoHSCT at failure to achieve remission after the 1st induction course CT is associated with the best 2-year OS (62 % vs. 35 %, p = 0,05), EFS (50 % vs. 22 %, p = 0,05) and RFS (50 % vs. 37 %, p = 0,05) in comparison with HDCT and sCT. In favorable cytogenetic risk group 5-year RFS was 80 % when performing autoHSCT and 67 % when performing HDCT; the 5-year OS was 80 % regardless of consolidation therapy option.Conclusion. AutoHSCT is the preferred consolidation option in favorable risk group patients, and after failure to achieve remission after the 1st CT course.